Exportations and competitiveness of poultry meat from Brazil and the state of Paraná, in the period between 1990 and 2005 Exportações e competitividade da carne de frango brasileira e paranaense no período de 1990 a 2005 - Vanderlei José Sereia; Marcia Regina Gabardo da Câmara; Luiz Gustavo Antonio de Souza (Semina: Ciências Sociais e Humanas, 2008)
The meat complex is one of the main components of the Brazilian export agenda. Poultry meat plays an important role in Brazilian exportations, being the State of Paraná the leader in this sector. The purpose of this work is to analyze the behavior and competitiveness of exportations in the agro-industrial poultry meat complex in Brazil and in the State of Paraná, in the period between 1990 and 2005, as well as the factors that determine the performance of Brazilian exportations and its interaction with the international trade. The Constant-Market-Share analysis was used, identifying the sources of agribusiness exportations growth complex, as follows: “worldwide market growth”, “export agenda elaboration”, “exportations destination” and “competitiveness”, which are able to express the behavior and pattern of exportations in the analyzed period. The geometrical growth rate method, by means of the Ordinary Least Square Method, was used to analyze the development of the complex in the period. In order to achieve the goals and verify the pattern of Brazilian exportations and the competitiveness of Brazilian poultry meat, data on worldwide exportations and importations of poultry meat in the period of 1990 to 2005 were gathered, so that it would be possible to identify the profile of the biggest consumer markets and the meat complex exporters. The analyzed data enabled us to conclude that the geometric growth rates of poultry meat increased in Brazil and in the State of Paraná, as well. The analysis of the CMS results shows that Brazil and the State of Paraná have high competitiveness and market-share in the analyzed segment. The increasing demand for this type of meat will enable Brazil to be consolidated internationally in this market, besides suggesting sanitary policies that might reduce barriers to the entrance of this product to the main import countries. O complexo de carnes é um dos principais componentes da pauta de exportação brasileira. As carnes de frangos apresentam grande participação nas exportações brasileiras, sendo que o Estado do Paraná é o maior estado produtor exportador do Brasil. O objetivo do trabalho é analisar o comportamento e a competitividade das exportações do complexo agroindustrial de carnes de frangos brasileiro e paranaense no período de 1990 a 2005, bem como os fatores que determinam o desempenho das exportações brasileiras e sua interação com o comércio internacional. O modelo principal de análise utilizado é o “Constant-Market-Share” que realiza a decomposição as fontes de crescimento das exportações dos complexos agroindustriais em componentes denominados: “crescimento do mercado mundial”, “composição da pauta de exportação”, “destino das exportações” e “competitividade” e são capazes de expressar o comportamento e padrão das exportações no período de estudo. O método da taxa geométrica de crescimento, por meio do Método dos Mínimos Quadrados Ordinários, foi utilizado para analisar a evolução do complexo no período. A fim de alcançar os objetivos e verificar o padrão das exportações brasileiras e a competitividade do frango brasileiro, foram colhidos dados sobre exportações e importações mundiais de carne dos anos de 1990 a 2005, de forma que se identificasse o perfil dos grandes mercados consumidores e exportadores do complexo carnes. Os dados analisados permitiram concluir que os indicadores do Brasil e do Estado do Paraná evoluíram a altas taxas de crescimento geométricas de carne de frango. A partir da análise dos resultados do modelo CMS, percebe-se que o Brasil e o Paraná possuem elevada competitividade e alto market-share no segmento analisado. A crescente demanda por este tipo de carne permitirá que o Brasil se consolide internacionalmente nesse mercado, além de serem sugeridas políticas sanitárias e outras que possam reduzir as barreiras à entrada deste produto nos principais países importadores.